Analysing Graduates' Motivations and Lived Experiences in a Graduate Programme in Bangladesh - Promy, Nabila Kamal (2019)
Need for fresh talents in organisational growth and sustainability is crucial; but attracting and retaining graduates in the workplace has become a global Human Resource Management challenge. Graduate programmes/schemes have been suggested as a panacea in this regard. In Bangladesh, different organisations are now considering graduate programmes as their key strategy in attracting and retaining fresh talents. However, in the academic field limited studies have looked at unique preferences of Bangladeshi graduates and graduate programmes’ role in motivating them. Thus, to unearth graduate programmes’ role, this study aimed at exploring Bangladeshi graduates’ motivations to join a graduate programme and their lived experiences working under such a programme. In doing so, this study took an inductive approach with focus on qualitative data. It was a case study where graduate programme of a telecommunication company in Bangladesh and its trainees were thoroughly analysed with primary and secondary data. Career growth opportunity, scope of changing career path, positive social perception about graduate schemes and compensation were found to be key reasons graduates preferred joining such a scheme. In-depth analysis of graduate trainees’ lived experiences revealed factors like welcoming organisational culture, friendly top management and recognition had significant positive impact on their experiences. Negative experiences related to people in the organisation, company’s stability and learning opportunity were also found. The study also highlighted some interesting paradoxes where single factor was found to have both positive and negative impact. Finally, raw suggestions from the participants shed some light on how such programmes can be further improved.